2003
DOI: 10.1002/mds.10614
|View full text |Cite
|
Sign up to set email alerts
|

Atypical propriospinal myoclonus with possible relationship to α interferon therapy

Abstract: We report on a man who received interferon-alpha 2a therapy for kidney cancer and who subsequently developed propriospinal myoclonus. The myoclonus was noted at rest and during movement. The jerks were reinforced by cutaneous stimuli and tendon taps and spread to the spinal cord via polysynaptic propriospinal pathways. Cerebrospinal fluid analysis, spinal cord magnetic resonance imaging, electroencephalogram with back-averaging, and somatosensory-evoked potentials were normal. No antineuronal antibodies were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Therefore, the EMG burst duration of our case may be considered as a relatively uncommon finding. However, there were also reports that polymyographic study of PMS revealed EMG burst durations of less than 200 ms [2,8,9]. Thus, the patient's polymyographic pattern generally met previously reported criteria.…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, the EMG burst duration of our case may be considered as a relatively uncommon finding. However, there were also reports that polymyographic study of PMS revealed EMG burst durations of less than 200 ms [2,8,9]. Thus, the patient's polymyographic pattern generally met previously reported criteria.…”
Section: Discussionmentioning
confidence: 53%
“…However, many of these reports did not check the data with the subject's state of mental activation. A few individual cases have been reported in which the movement seemed to be elicited by standing or changing position [27,30,41,42]. 14,15].…”
Section: Clinical Featuresmentioning
confidence: 96%
“…Different pharmacological treatments have also been associated with PSM onset, i.e., interferon-alpha [30], intrathecal bupivacaine [31,32], ciprofloxacin [33] and cannabis [34].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…42 Furthermore, 2 PSM cases were related to drug abuse, 1 involving cannabis 29 and 1 with N 2 0 and vitamin B 12 deficiency. 53 Finally, secondary PSM was reported in 2 cases with a possible toxin from Escherichia coli 22 and 4 secondary to administered medication, being interferon, 19 ciprofloxacin, 38 bupivacaine, 54 and 1 after multiple drugs for a cesarean section. 27 Of note, temporal links between onset of PSM and reported causality were variable.…”
mentioning
confidence: 99%